Minimum degree conditions for monochromatic cycle partitioning - Korándi, Dániel; Lang, Richard; Letzter, Shoham; Pokrovskiy, Alexey (Journal of combinatorial theory, 2021)
A classical result of Erdős, Gyárfás and Pyber states that any r-edge-coloured complete graph has a partition into O(r2log⁡r) monochromatic cycles. Here we determine the minimum degree threshold for this property. More precisely, we show that there exists a constant c such that any r-edge-coloured graph on n vertices with minimum degree at least n/2+c⋅rlog⁡n has a partition into O(r2) monochromatic cycles. We also provide constructions showing that the minimum degree condition and the number of cycles are essentially tight.